KONSEP MOTIVASI DASAR, MOTIVASI KERJA DALAM PENDIDIKAN DI MADRASAH ALIYAH SUNAN KALIJAGA - Sony Eko Adisaputro (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
Motivation is the most basic factor in educational institutions to mobilize the potential of human resources to foster enthusiasm in working with organizational goals. The second factor is the leader as a leader who is able to mobilize human resources. Sensitivity leaders are expected to understand the nature and human needs. The hierarchy of human needs is expected to be another consideration in motivating staff, teachers (ustadz) or employees. Five things human needs that need to be considered are: physiological, safety, social, esteem and self-actualization needs. If a leader puts forward human values ​​in motivating his subordinates, then productivity and success can be realized in the institution or agency he leads.